2015
DOI: 10.3126/ijasbt.v3i3.12924
|View full text |Cite
|
Sign up to set email alerts
|

Extended Spectrum Beta Lactamases Detection and Multiple Antibiotic Resistance Indexing of Escherichia Coli from Urine Samples of Patients from a Referral Hospital of Eastern Nepal

Abstract: Background: Escherichia coli is the most common causative agent of urinary tract infection. Antibiotic resistance among uropathogens has become a prominent public health problem. Multidrug resistance bacteria have limited the therapeutic possibilities by producing Extended Spectrum Beta Lactamases (ESBL). Objective: Since routine monitoring of ESBL producers are not conducted in clinical laboratories their true prevalence is still unknown. So the objective of this research was to assess multiple antibiotic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
1
6
1
Order By: Relevance
“…A study by Ghimire et al [ 21 ] and Yadav et al [ 46 ] recorded 96.8% and 82.5% of the isolates as MDR, respectively. Guragain et al [ 39 ], Chakravarti et al [ 47 ], and Sharma et al [ 48 ] reported a lower MDR rate than ours in urinary E . coli and K .…”
Section: Discussioncontrasting
confidence: 39%
“…A study by Ghimire et al [ 21 ] and Yadav et al [ 46 ] recorded 96.8% and 82.5% of the isolates as MDR, respectively. Guragain et al [ 39 ], Chakravarti et al [ 47 ], and Sharma et al [ 48 ] reported a lower MDR rate than ours in urinary E . coli and K .…”
Section: Discussioncontrasting
confidence: 39%
“…The disks were placed 20 mm apart. A > 5 mm increase in a zone diameter for antimicrobial agent tested in combination with clavulanic acid versus its zone when tested alone are ESBL producers [17,24] .…”
Section: Combined Disk Methodsmentioning
confidence: 99%
“…However, a low resistance rate in both ESBL positive and negative E. coli were demonstrated against amikacin, imipenem and nitrofurantoin, In pregnant women, the MDR mean value was significantly (t=4.26, P=0.0001) higher in ESBL producer E. coli (6.38±1.13) than that in ESBL negative E. coli (5.09±1. 19). In addition, in diabetic women, the MDR mean value was significantly (t=3.41, P=0.0013) higher in ESBL producer E. coli (6.92±0.98) than that in ESBL negative E. coli (5.75±1.22).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study in Erbil, Iraq [8], MDR was more predominant in ESBL positive E. coli than in ESBL negative isolates and 71.89% of ESBL positive isolates show MDR of ≥5 antibiotic groups, while the corresponding value in ESBL negative was 40%. Cruz et al [29], 2014, Philippines, reported that MDR to 4 antibiotic groups, while Chakrawarti et al, [19], 2015, Nepal, reported nine MDR patterns for E. coli isolates. In addition, Aka and Haji, [40], 2015, Erbil, Iraq, reported that they found MDR more frequent in ESBL positive E. coli isolates; however, their data are multiple antibiotic resistance number and not MDR trend.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation